Effects of medication intake in early pregnancy on the fetal fraction of cell‐free DNA testing. (27th February 2019) - Kuhlmann‐Capek, Maggie; Chiossi, Giuseppe; Singh, Prapti; Monsivais, Luis; Lozovyy, Violetta; Gallagher, Lauren; Kirsch, Nathan; Florence, Elizabeth; Petruzzi, Victoria; Chang, Jeffrey; Buenaventura, Sofia; Walden, Paul; et al.
Abstract: Objectives: To determine the association between medications intake in early pregnancy and variation in the fetal fraction (FF) in pregnant women undergoing cell‐free DNA (cfDNA) testing. Methods: We performed a retrospective cohort study of women ( n = 1051) undergoing cfDNA testing at an academic center. The exposed group included women taking medications ( n = 400; 38.1%), while the nonexposed group consisted of women taking no medications ( n = 651; 61.9%). Our primary outcome was FF. We performed univariate and multivariate analyses as appropriate. Results: The FFs were 8.8% (6.6‐12.1), 8.7% (6.3‐11.6), and 7.7% (5.1‐9.3) among women taking 0, 1, and two or more medications, respectively ( P < 0.01). Using multivariable linear mixed effects model, the mean FF was significantly lower among those taking two or more medications compared with the nonexposed group. FF was directly correlated with gestational age at the time of cfDNA testing and inversely correlated with maternal obesity. Exposure to metformin was associated with 1.8% (0.2‐3.4) lower mean FF when compared with the nonexposed group ( P = 0.02). Obesity and intake of two or more medications were associated with higher hazard ratio of having a low FF less than 4%. Conclusions: Exposure to metformin or two or more medications was associated with decreased FF, and obesity is associated with delay in achieving adequate FF percentage. These findings should be considered while counseling patients on test limitations. Abstract : What is already known about this topic? Several factors have been reported to affect the fetal fraction of cell‐free DNA noninvasive prenatal testing. While there are reports that heparin may affect the fetal fraction and may lead to false‐negative results for Down syndrome, there are sparse data from larger studies on the effect of medications intake in pregnancy on fetal fraction. What does this study add? This study investigates heparin, as well as other commonly used classes of medications, in regard to their effect on fetal fraction at the time of noninvasive prenatal testing. We report that metformin may have a significant effect on the fetal fraction. We also confirm previous findings regarding the effects of obesity and gestational age at testing on fetal fraction.